Impact Assessment of Radio Frequencies Field Levels of Some GSM Base Stations in Makurdi Metropolis - Iortile, J.T; Agba, E.H; Ujah, F.O (International Journal of Natural Sciences Research, 2013)
The radio frequency field levels of some Globacom and MTN telecommunications base stations in Makurdi metropolis were measured using electromagnetic field tester (EMF827 Lutron). Measurements were done at distances of 5.00, 10.00, 15.00 and 20.00 metres away from the base stations in the north, south, east and west directions. The electric field intensity and specific absorption rate (SAR) were calculated with references to some human tissues. The results show the average magnetic field levels of MTN and GLO base stations to range between 0.09µT to 0.16µT. The mean electric field values for eye, brain and muscles ranged between 18.81υm-1 to 35.20υm-1. The specific absorption rate (SAR) values for the selected human tissue were found to range between 0.18Wkg-1 to 1.17Wkg-1. The results of the research denote that the radiations emitted by GSM base stations conform to the standards set by regulatory bodies, as such; there are no inherent danger to residents found within the base station areas.